Circulating micromegakaryocytes in myelodysplasia. Issue 11 (November 1987) - Erber, W N; Jacobs, A; Oscier, D G; O'Hea, A M; Mason, D Y
Abstract : The alkaline phosphatase-antialkaline phosphatase (APAAP) immunocytochemical staining technique was used to look for circulating cells of megakaryocyte lineage in peripheral blood smears from 67 cases of myelodysplasia. Small numbers of micromegakaryocytes positive for platelet glycoprotein IIIa were found in 23 cases. These cells superficially resemble small lymphoid cells and are hence difficult or impossible to recognise in conventional Romanowsky stained smears. Circulating micromegakaryocytes were found most commonly in more aggressive types of myelodysplasia (such as refractory anaemia with excess blasts (RAEB) and refractory anaemia with excess blasts in transformation (RAEB-t], and their presence may therefore indicate a poor prognosis. Because of the simplicity of this immunocytochemical labelling technique, it could be of wide use in the initial assessment of patients with myelodysplasia, and possibly for the early detection of acute leukaemic transformation.